2000
DOI: 10.1002/1098-108x(200012)28:4<451::aid-eat14>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thiamin deficiency in anorexia nervosa

Abstract: Objective Deficiency of thiamin (vitamin B1) causes a range of neuropsychiatric symptoms that resemble those reported in patients with anorexia nervosa (AN) but the prevalence of thiamin deficiency in AN has not been reliably established. This study was designed to investigate the prevalence of thiamin deficiency in AN. Method Thirty‐seven patients attending a specialist eating disorders unit and meeting all or some of the DSM‐IV criteria for AN were compared with 50 blood donor controls. All subjects underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 12 publications
0
50
0
2
Order By: Relevance
“…However eating orders in general lead to changes in electrolyte content and associated whole-body organ dysfunction including the heart. Hypotension and sinus bradycardia is common in AN [9]. This probably results from elevated parasympathetic tone, which occur to compensate for the starvation activity along with reduced metabolic expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However eating orders in general lead to changes in electrolyte content and associated whole-body organ dysfunction including the heart. Hypotension and sinus bradycardia is common in AN [9]. This probably results from elevated parasympathetic tone, which occur to compensate for the starvation activity along with reduced metabolic expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, repolarisation abnormalities and prolongation of ECG Q-T interval are thought to be associated with ventricular arrhythmia and severe weight loss [26,32]. However, a number of studies of HRV have confirmed that these structural and functional abnormalities of the cardiovascular system provoked by AN are reversible after weight restoration [9,25,28,29,33]. This study indicated that HRV in ED patients is lower than control, especially HRV complexity measured by Sample Entropy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, dado que en la anorexia nerviosa se han descrito innumerables carencias nutricionales, en dicha situación podrían necesitarse. Así ocurre con el calcio ante el rechazo de los lácteos 36 , el hierro en pacientes vegetarianos y/o con excesivo ejercicio 54,55 , el zinc si hay escasa ingesta de carne y/o ejercicio excesivo 56,57 , la tiamina y el ácido fólico si existe abuso de alcohol 58,59 y la vitamina D si hay rechazo de lácteos y/o baja exposición solar 60 . En relación con los déficits de tiamina se han recogido complicaciones como el síndrome de Wernicke 61 .…”
Section: Uso De Suplementosunclassified
“…Alterations in sympathetic and parasympathetic regulation of the heart as a response to oxidative stress and inflammation, electrolyte and body-water disturbances, muscular damage, renal disease and structural changes of the heart have also been observed in AN [13,14].…”
Section: Introductionmentioning
confidence: 99%